FORMATION OF ENVIRONMENTAL CULTURE AND KNOWLEDGE IN STUDENTS - Uzoqjonova Moxinur (Western European Studies, 2024)
This article presents the system of development of environmental knowledge and culture among students, pedagogical methods and recommendations for their improvement.
Keywords: Ecological culture; ecological knowledge; inductive